PARTISIPASI PEREMPUAN DALAM PERBANKAN SYARIAH - Rahim, Abdul (PSW, 2010)
Women participation in banking of moslem law in this case very good high entrepreneur area in small industry like mixture sell, merchant and cloister at traditional market. This matter indicated that the women do this effort to show to family or husband. The women also deflect to follow to take a hand in thinly family to the field of economics. Even dive this small effort economics is household head or husband however woman also follow to assist even show the obstinacy of ind the field of effort.But some constraints faced women in the field of this effort not other in educational, where women hardly do cooperation banking of moslem in developing the effort. Women that form education aspect of where most women which plunge the less effort area education of only just elementary school, there event exist which not at all go to school. All this become causes of constraint to do the menâs effort.For example which become many constraints for women in doing the effort business that is problem of culture, where our culture in general women only thin family and child not be anabled to do the menâs effort that anything else many house exists causing mussy family.